REFORMA A LA LEY REFORMATORIA DEL CÓDIGO ORGÁNICO DE LA NIÑEZ Y ADOLESCENCIA EN SU ATÍCULO INNUMERADO 10 SOBRE LAS OBLIGACIONES DEL PRESUNTO PROGENITOR O PROGENITORA - Vargas Mendoza, Jonathan Vicente (2015)
This research work is to focus on an event of significant importance in the social living and the very existence of the human race and conservation, as it is the birth of a human being and the intangible right to protection from their parents and the State; kinship and biological link are determined by DNA testing, to thereby establish paternity and kinship, in order to establish their responsibility and obligation in providing food. In our current Code of Childhood and Adolescence, clearly it determined that protect the rights and protect children and adolescents; just as the rights and duties of parents towards their children are established; and, having established two cases of utmost importance within the Judicial Specialized Unit of the Family, Women, Children and Adolescents den Canton Loja, where an existing legal vacuum is evidence in relation to the control of times the mother may request DNA testing in trials of presumption of paternity and delivery of food, reaching by the judge to have up to 7 times in one and up to three times in a second case with a negative result in this test DNA processes that I will make known later. Considering effectively so necessary to propose an amendment to Title V Chapter II, unnumbered article 10 of the Law Amending the Code of Children and Adolescents, with the inclusion of a clause to control the times that the mother can apply for practice DNA testing; considering that the plaintiff acts maliciously by not diligently to that which results in the expansion process, and 5 there is a violation and disrespect for the rights of equality and opportunity defendant enshrined in the Constitution, also causing damage economic canceling the defendant to be alimony that does not belong not to be the biological father of the child and in the same way the State as public resources are being used. . The paper will analyze the implementation and application of constitutional principles such as speed and simplify the process, among others, resulting in the conception of respect for the rights to equality before the law and its correct application in the food and judgments acknowledgment of paternity having very clear above all, food is a right of children and "formalities" cannot affect that right as well misapplication nor the judge can disrespect the rights dl common citizen.